Thirty years in anesthesiology: A bibliometric analysis - Tümer, Murat; Öztürk, Talih; İzgi, Murat and Yalçın, Haydar (Acta Medica, 2023)
Background: The number of publications on anesthesiology continues to increase. Although there are studies conducted about this increase, they are insufficient to show the direction and structure of the changes. This study aimed to investigate the conceptual structure and thematic evolution in publications about anesthesiology over the last 30 years. Methods: In this study we made a systematic reviews and bibliometric analyses of observational and Randomized Controlled Trial (RCT) studies. Bibliometric analysis was used to reveal thematic clusters by associating keywords and relationship patterns in three periods. Thematic clusters were revealed using a science mapping analysis based on co-word networks and strategic diagrams created according to centrality. Density values were used to determine the positions of the clusters. A total of 119,842 articles published between 1990 and 2022 in the anesthesiology category of the Web of Science (WOS) Core Collection were analyzed. Articles published before 1990 and/or not in the WOS Collection were excluded from the study. Results: Seven thematic areas were identified over three time periods: Pain, Medications, Regional Anesthesia, Cardiovascular Anesthesia, Pediatric Anesthesia, Critical Care, and Airway Management. Over the years, motor themes have been shaped by new anesthetic agents and techniques. Pain and Regional Anesthesia have been the most researched topics. Patient Safety, Elderly Patients, and Palliative Care were the emerging themes in the last years. Critical Care thematic area moved to Mortality, Mechanical Ventilation, and COVID-19. Conclusion: Pain is the most popular topic over the last 30 years. Increasing of themes like Patient Safety and Palliative Care in the last years may be related to the increasing quality management awareness and the older population. The fact that the COVID-19 thematic area has a large place in last period shows the effect of the pandemic in the field of anesthesiology.